MATEC Web of Conferences - Kvesko; Kornienko; Petrunina; Kabanova Specialist in the field of engineering pedagogy Leading manager of Tomsk Polytechnic University? (2018)
The paper dwells on the prognosis of the social systems development. The prognostic analysis is based on the systemic approach to the issue; it shows that the conditions of the transference to the knowledge society determine the formation of the brand new features in social prognoses. The paper states the specific features and conditions of social prognosis, which ensure the validity of control actions. Besides, the current analysis provides recommendations on how to devise social prognostic strategies (within the frame of a) transference to the knowledge society and b) environmental instability). Finally, the functional load of social prognosis in the contemporary conditions is outlined.